Integrating Halal Nutraceutical Product Development with Religious Mentoring in a Convert-dominant Farming Community - Zainal Arifin; Junaidi, Junaidi; Moh Holil Baitaputra; Mufaizin, Mufaizin; M. Tohir (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
In a convert-dominant Muslim community surrounded by a Christian majority in rural East Java, Indonesia, organic vegetable farmers face two intersecting challenges: low economic value from unprocessed produce and weak religious mentoring due to economic pressures. This community empowerment study aimed to integrate halal nutraceutical product training with Islamic religious mentoring to enhance both entrepreneurial skills and religious participation among 10 female farmers from the